Incidence and Visual Outcomes of Endophthalmitis After Intravitreal Injection of Dexamethasone Implant vs Ranibizumab. (September 2022) - Pancholy, Maitri; Storey, Philip P.; Wood, Edward H.; Chaudhary, Varun; Obeid, Anthony; Marlow, Elizabeth; Farley, Nathan D.; Wolfe, Jeremy D.; Garg, Sunir J.
Purpose: To compare the incidence and visual outcomes of endophthalmitis after injection of an intravitreal dexamethasone implant and injection of intravitreal ranibizumab. Methods: This retrospective cohort study assessed endophthalmitis in eyes receiving an intravitreal injection of a 0.7 mg dexamethasone implant (DEX group), 0.5 mg ranibizumab (R5 group), or 0.3 mg ranibizumab (R3 group) between January 1, 2016, and May 31, 2018, at 2 large retina practices in the United States. Results: Suspected endophthalmitis occurred in 5 eyes after 4973 DEX injections, 43 eyes after 163 974 R5 injections, and 6 eyes after 18 954 R3 injections. Suspected endophthalmitis was significantly more common in the DEX group (1/995) than in the R5 group (1/3813) ( P  = .008) but not than in the R3 group (1/3159) ( P  = .10). Visual acuity outcomes were similar in the 3 groups. Conclusions: Suspected endophthalmitis might be more common after 0.7 mg dexamethasone injections than after 0.5 mg ranibizumab injections. Culture-positive endophthalmitis rates were similar across all 3 medications.